Recent Advances in QSAR-based Identification and Design of Anti-Tubercular Agents - Nidhi; Imran Siddiqi, Mohammad (Current Pharmaceutical Design, 2014)
Increasing worldwide incidence and the advent of multi drug resistant and extensively drug resistant tuberculosis raise the need of new drugs for the treatment of tuberculosis soon. To meet the required pace QSAR-based rational approaches may prove fruitful as they render rapid and cost-efficient design and optimization of new drug candidates. This review presents a comprehensive overview of QSAR studies reported for newer anti-tubercular agents including nitroimidazoles, fluoroquinolones, quinoxalines, carboxamides and other classes of molecules. The article includes review of 2D and 3D-QSAR approaches and the recent trend of integration of these methods with virtual screening using 3D pharmacophore and molecular docking approaches for the identification and design of novel anti-tubercular agents.
Keywords: CoMSIA